Appraisal Analysis of Judgment of English Billboard Advertisements on Roads in Batam - Suswanto Ismadi Megah S; Siti Noor Fazelah Mohd Noorh (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2018)
This study investigates appraisal analysis of the judgment in the English boradboard advertisement on roads in Batam. This choice of judgment by leaving affect and attitude  is to focus on judgment of the advertisement makers in making perspective buyers are interested to buy their products on around roads in Batam.  The framework of this study by employing of appraisal theory which was firstly introduced by Martin (1996,2000, and 2003). This theory is   to analyze the evaluation of judgment of English billboard on roads in Batam.  The data analyzed qualitatively.  Due to research can be definite as a systematic observation analysis and objectively based on theory we can get the right result from events in special design .There were 11 data found. The data found that there were 6 personal judgments and 5 moral judgments. The personal judgment is more than moral judgment than personal judgment. This study concluded that the positive personal judgment of advertisement found mostly by admiring the product.